(3QSGdI aj GdQHY GdJGe GdehVhY dehGbjJ GdESdGes - (3GdCfUGQj, CHh GdMSf, GHf GdTGWQ, YdGA GdOjf, Ydi Hf EHQGgje Hf eMeO, (B777 (3g`s ((3YKeGf Hf eMeOs)
(3ChdgG (B:s
(3GdMeO ddg MeOG jdjb HLdGdghHYO agPg QSGdI CPcQ ajgG CSeGA GdQShe GdeQShe Ydi GdBdI GdeSeGI HGdGSWQdGH GdTeGdj PGJ GdUaGFM hHYV CYeGdgGs
(3BNQgG (B:s
(3fGbU GdBNQ, hBNQg(B: (3NGJeI aj eYQaI GdeWGdY hJShjI GdHjhJ GdGKfj YTQ hgj Cf JVY LRA GdTeS Ydi ebOGQ GdGQJaGY GdeCNhP aj GdhbJ GdeaQhV ef YOO GdebfWQGJ aeG hbY ef Cabs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 251s
(3eYLe GdeDdajf(B: 2 / 389s
(3cTa GdXfhf(B: 1 / 866s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3gjFIs